Biological aspects of Crematogaster spp. (Hymenoptera: Formicidae) predator of Leptopharsa gibbicarina (Hemiptera: Tingidae) in oil palm Elaeis guineensis - SALAMANCA-O., JUAN CARLOS; CALVACHE-G., HUGO; DE LA TORRE, JORGE ALDANA; MESA, NORA CRISTINA; MÉNDEZ-S, ADALBERTO (Revista Colombiana de Entomología, 2000)
Leptopharsa gibbicarina Froeschner is one of the most serious pests of oil palm. for being the principal promoter of Pestalotiopsis. it’s found that the ants of genus Crematogaster spp. (Formicidae - Mirmicinae) is one of the most important plunderers since as it lowers the lace bug female populatíon. for that reason it’s necessary to know the ant’s nest disposition, in the space and in the oil palm stem. This work was made in Guayabos farm in Ciénaga (Magdalena). between August 1997 -April 1998, in a ground that was put 59 Crematogaster colonies in each 5 lines by 5 palms according to the 170 established colonies in a natural way. The evaluatíons were made palm by palm looking at the behavior of the ant and quantify the lace bug female population in two palm leaves. The colonies get on 116.15% in these conditions with a contagious distribution initial and later with a tendency to a random distribution.